Electrospun Structures Made of a Hydrolyzed Keratin-Based Biomaterial for Development of in vitro Tissue Models - Fortunato, Gabriele Maria; Da Ros, Francesco; Bisconti, Samuele; De Acutis, Aurora; Biagini, Francesco; Lapomarda, Anna; Magliaro, Chiara; De Maria, Carmelo; Montemurro, Francesca; Bizzotto, Dario; Braghetta, Paola; Vozzi, Giovanni (Frontiers in Bioengineering and Biotechnology, 2019)
The aim of this study is the analysis and characterization of a hydrolyzed keratin-based biomaterial and its processing using electrospinning technology to develop in vitro tissue models. This biomaterial, extracted from poultry feathers, was mixed with type A porcine gelatin and cross-linked γ-glycidyloxy-propyl-trimethoxy-silane (GPTMS) to be casted initially in the form of film and characterized in terms of swelling, contact angle, mechanical properties and surface charge density. After these chemical-physical characterizations, electrospun nanofibers structures were manufactured and their mechanical properties were evaluated. Finally, cell response was analysed by testing the efficacy of keratin-based structures in sustaining cell vitality and proliferation over 4 days of human epithelial, rat neuronal and human primary skin fibroblast cells.